Modelo multivariable para la planificación del entrenamiento en fútbol profesional - Chena Sinovas, M.; Morcillo Losa, J. A.; Rodríguez Hernández, M. L.; Zapardiel, J. C. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2022)
The aim of this study was to describe a multivariable training planning model for weekly monitoring and its periodization in relation to the dynamic competitive profile. Twenty-two professional soccer players participated in this study. Thirty competitive microcycles were analyzed. Thirty competitive microcycles were recorded individually in all training sessions and competition matches through a GPS device. The results showed a loading phase with values close to those achieved in competition, but with differentiated stimuli on consecutive days, and another phase of load reduction in the form of tapering prior to competition. The weekly accumulated load showed little variability between the microcycles; an average of 0.6% was observed. Dynamic load management presented an A: C ratio that ranged from 0.89-1.13. It can be concluded that the multivariate model for planning weekly training is an effective method to monitor training load in relation to performance profile